Educación General y Aprendizaje Liberal. Principios de prácticas efectivas - Haché, Ana Margarita (Cuaderno de Pedagogía Universitaria, 2014)
Se reseña el libro General Education and Liberal Learning: Principles of Effective Practice. Este libro explora elementos comunes a los programas de Educación General y analiza cómo esos programas promueven el aprendizaje liberal, aspecto esencial para la educación del siglo veintiuno. La publicación expone los cambios que han ocurrido en los programas de Educación General, con énfasis en la Educación Superior. Se discute, también, cómo las instituciones pueden mejorar sus prácticas en estos programas a través de reportar ejemplos exitosos. El libro es útil para los comités de currículum y para todos los grupos que trabajen en evaluar programas de Educación General. This is a book review of General Education an Liberal Learning: Principles of Effective Practice. This book explores elements common to strong general education programs and examines how strong programs support liberal learning outcomes essential to success in the twenty-first century. The publication surveys the changes that have occurred in general education programs —and more broadly in higher education. The publication discusses also how institutions may improve their general education practices and provides numerous examples of successful practices. The book is useful for curriculum committees and any group of professionals that work on the assessment of General Education programs.